(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Proteus mirabilis is an important opportunistic human pathogen capable of causing a wide range of infections. With MDR P. mirabilis infections on the rise, especially on those underwent long-term indwelling urinary catheterization, the need for a rationally designed vaccine against this pathogen is critical. This study was conducted to evaluate the protective efficacy of antibodies elicited by formalin inactivated vaccine against MDR P. mirabilis and to observe the memory B cell response for future protection. Materials and methods: In this experimental study, MDR P. mirabilis isolated from different clinical samples were used in preparing formalin inactivated whole-cell P. mirabilis and employed Intradermally (I/D) in experimental group (Group-1) mice thrice at 14 days interval. Two weeks after 3rd dose of immunization, group-1 and group-2 mice were intraperitoneally challenged with live P. mirabilis and observed for 14 days. Tail blood was collected 7 days after each booster and followed by cardiac puncture 14 days post challenge. Antigen binding capacity of the protective IgG was determined by ELISA and memory B cell evaluation was done on RPMI media. Results: All immunized mice in group-1 (100%)survived after the lethal dose of live P. mirabilis. When antigen binding capacity was evaluated by ELISA, all the prechallenge and post challenge immunized serum IgG antibody of experimental group mice showed significantly higher Optical Density (OD) values compared to the OD values of control mice sera.Blood was collected from group-1 and negative control (Group-3) by cardiac puncture14 days post challenge. Peripheral Blood Mononuclear Cells (PBMCs) were separated from the blood by using density gradient centrifugation on Ficoll-isopaque, and incubation of the cells were done in RPMI media. Cell culture supernatant samples were used from each group to measure IgG antibody absorbance by ELISA to evaluate memory B cell response. Conclusion: Statistically significant difference between the OD values of experimental and control mice cell culture supernatant was observed which is suggestive of significant production of memory B cells that might provide long term immunity for combating MDR P. mirabilis infections. Chatt Maa Shi Hosp Med Coll J; Vol.25 (1); January 2026; Page 95-100